The Family Environment's Impact on Human Values in Progressive Islamic Education - Suud Sarim Karimullah (Fakultas Ilmu Tarbiyah dan Keguruan (FITK), Institut Agama Islam Negeri (IAIN) Surakarta, 2023)
This study aims to investigate in depth the influence of the family environment on understanding human values in the context of progressive Islamic education. This study relies on library research involving integrative and comprehensive literature analysis to investigate various literature sources that are relevant to the topic of study. The results of this study stated that the family environment plays a vital role in shaping the understanding of human values in progressive Islamic education. The positive part of the family in conveying these values to children is essential in ensuring that future generations will grow up as individuals who are aware of the importance of humanity, tolerance, and justice in their religion and daily lives. When families integrate these values into everyday interactions and communication, children have a greater chance of internalizing those values and creating more inclusive and equitable individuals in the future.